2023
DOI: 10.3390/foods12122318
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Nitrogen Forms on Blackberry Fruit Quality

Abstract: To study the optimal form of nitrogen (N) application and to determine the best harvest date for blackberries, different N fertilizers were applied during the critical growth period of blackberry plants. The results showed that NH4+–N significantly improved the appearance of blackberry fruits, including their size, firmness, and color, and promoted the accumulation of soluble solids, sugars, anthocyanin, ellagic acid, and vitamin C (VC), while fruit treated with NO3−–N accumulated more flavonoids and organic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…This was likely related to the low TPC found in the same samples. Duan et al similarly found that blackberries under NO 3 -N stimulated DPPH activity [45]. On the contrary, amaranth species supplied with NH 4 -N exhibited superior DPPH activity [43].…”
Section: Effect Of N Rate and Form On Radical Scavenging Activitymentioning
confidence: 97%
“…This was likely related to the low TPC found in the same samples. Duan et al similarly found that blackberries under NO 3 -N stimulated DPPH activity [45]. On the contrary, amaranth species supplied with NH 4 -N exhibited superior DPPH activity [43].…”
Section: Effect Of N Rate and Form On Radical Scavenging Activitymentioning
confidence: 97%
“…Both consumers and food suppliers place a great deal of importance on fruit quality, with premium fruits typically having greater market potential. As a result, berry growers worldwide seek berries that are large, firm, flavorful, and nutrient-rich [26]. With their bioactive components, which include phenolic acids and flavonoids [27], they have strong antioxidant activity [28] and help prevent a variety of ailments.…”
Section: Introductionmentioning
confidence: 99%
“…The main advantage of blackberry culture is the unique taste and useful properties of the fruits, which depend on the amount of sugars and organic acids in the berries, and are more related to their genotype [2]. In the studies of Makarkinoy M.A., the genotypes of 'Black Satin', ' Čačanska Bestrna', 'Chester', 'Natchez', 'Triple Crown', ELS LN-14, OS LN-1, and OS LN-7 were chosen as the blackberries with a high content of bioactive substances in the fruits, namely ascorbic acids and phenolic compounds [3][4][5].…”
Section: Introductionmentioning
confidence: 99%